Assessment of Psychosomatic Risk in a Kidney Transplant Recipient: A Clinical Study within the Framework of Integrative Psychosomatics - Bilal, KHERBOUCHE; Zahia, IKARDOUCHENE (Journal of Posthumanism, 2026)
Although kidney transplantation improves survival and autonomy for patients with end-stage renal disease, it is a significant transition that comes with a lot of psychological difficulties. Integrative approaches have not sufficiently examined the psychosomatic mechanisms underlying post-transplant vulnerability. Based on Jean-Benjamin Stora’s integrative psychosomatic model, this qualitative single-case study examines Sadia’s functioning after her transplant. The results emphasise psychosomatic vulnerability, which is typified by medical hypervigilance, narcissistic fragility, and limited affect elaboration. From a non-dichotomous perspective, clinical graft success does not in itself guarantee stabilization of the overall equilibrium: relational fragilities and chronic stress continue to influence the regulatory dynamics of the psychosomatic whole. This study aims to explore psychosomatic functioning in a kidney transplant recipient through Storas integrative framework, with particular attention to affect regulation, object relations, and psychosomatic risk.